2018
DOI: 10.1186/s13071-018-3150-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental variables and kdr resistance genotype on survival probability and infection rates in Anopheles gambiae (s.s.)

Abstract: BackgroundEnvironmental factors, especially ambient temperature and relative humidity affect both mosquitoes and malaria parasites. The early part of sporogony is most sensitive and is affected by high temperatures and temperature fluctuation immediately following ingestion of an infectious blood meal. The aim of this study was to explore whether environmental variables such as temperature, together with the presence of the kdr insecticide resistance mutations, have an impact on survival probability and infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 53 publications
3
20
1
Order By: Relevance
“…[5,51]). Similarly, that permethrin exposure did not affect the longevity of individually reared mosquitoes corroborates studies that found no or negative effect of insecticide on post-infection survival following larvicidal (Bti) [19] or pyrethroid exposure [15,52]. However, in our experiment mosquitoes that were exposed both as larvae and as adults survived longer than unexposed ones, if they had been reared with competition.…”
Section: Mosquito Longevity Post-infectionsupporting
confidence: 92%
See 1 more Smart Citation
“…[5,51]). Similarly, that permethrin exposure did not affect the longevity of individually reared mosquitoes corroborates studies that found no or negative effect of insecticide on post-infection survival following larvicidal (Bti) [19] or pyrethroid exposure [15,52]. However, in our experiment mosquitoes that were exposed both as larvae and as adults survived longer than unexposed ones, if they had been reared with competition.…”
Section: Mosquito Longevity Post-infectionsupporting
confidence: 92%
“…However, exposure to permethrin at either larval or adult mosquitoes reduced both the prevalence of infection and the mosquitoes' infectiousness. These results corroborate several studies that found lower Plasmodium infection prevalence after adult mosquitoes were exposed to deltamethrin (a pyrethroid) [14,15,52], bendiocarb (a carbamate) or DDT (an organochlorine) [53] (but see [54]). Our findings also complement these results by showing that exposure at larval and adult stages, even at a very low dose, have similar effects on infection prevalence.…”
Section: Infection Prevalence and Intensitysupporting
confidence: 91%
“…In addition, while we found no effect of permethrin exposure on mosquitoes reared individually, those reared in competition had an increased longevity when they were exposed both as larvae and as adults. These results do not support previous studies that found no or negative effect of insecticide on post-infection survival following larvicidal (Bti) (95) or pyrethroid exposure (128,237). Indeed, our results suggest that the insecticide may positively interact with mosquito immunity (as suggested by the results on prevalence) and alleviate the costs of the infection.…”
Section: Longevity Post-infectioncontrasting
confidence: 99%
“…These results are in accordance with several studies that found reduction of Plasmodium infection prevalence after adult mosquitoes were exposed to deltamethrin (pyrethroids) (128,223,237), bendiocarb (carbamate) or DDT (organochlorine) (119) (but see ( 238)). Our findings corroborate and complements these results by showing that exposure at both larval and adult stages -even at very low dose-have similar effects on infection prevalence.…”
Section: Parasite Prevalencesupporting
confidence: 92%
“…Gametocyte-infected mosquitoes must survive long enough to become infectious and transmit the sporozoites to a new host [60]. So, one of the key factors modulating malaria transmission is the vector longevity post blood feeding.…”
Section: Discussionmentioning
confidence: 99%